Pengembangan Instrumen Penilaian Keterampilan Proses Berbasis Sains Pada Materi Sistem Indra - Sholihah, Fatikhatun Nikmatus; Wulandari, Anggun; Hidayah, Wahyu Nurul (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2022)
Science based process skills are those that involve the use of tools and materials and interact in learning activities. The research was back to back by needs analysis questionnaire that science teacher and biology teacher never did a skill assessment but not yet applied a science based process skill assessment and the science teacher has applied science but hasn’t practice. The research aims to describe the feasibility of a science based process assessment instrument on the material of the sensory system developed. This development has been using the 4D model namely Define, Design, Develop, Disseminate. but at this stage of disseminate of cost limitations and time. The data collection instruments used included a questionnaire on the needs of educators, an expert validation questionnaire and an expert validation questionnaire. The results of the expert validation of the assessment instrument obtained a percentage of the feasibility of the science based process skills assessment instrument is 72.72% with feasible criteria, and the results of the material expert’s validation percentage of eligibility is 93.75% with worth it criteria. The research conclusion describes the feasibility of a science based process assessment instrument on the developed sensory system material that is worthy of use.